Peran Ilmu Komputer dalam Pembelajaran Bahasa Indonesia - Tia Risky Yasmin Saketang; Dinda Syafitri; Sahara Lani Lestari; Kayla Amelia Putri (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The advancement of digital technology has driven a fundamental transformation in the ecosystem of Indonesian language learning. This study aims to examine the role of Computer Science in supporting and modernizing Indonesian language learning in the digital era, identify Computer Science-based technologies that have been applied, and analyze the challenges and opportunities of their integration. This study employs a literature review method by analyzing twelve national scientific journals published between 2021 and 2025. The findings indicate that Computer Science contributes multi-dimensionally through sub-fields of Natural Language Processing (NLP), artificial intelligence (AI), gamification, and educational software engineering. Key findings include: (1) NLP for the Indonesian language has encompassed stemming, POS tagging, and syntactic parsing as the foundation for automatic correction systems and automated essay scoring; (2) algorithm-based gamification has proven effective in increasing student motivation and active engagement; (3) AI-based learning platforms enable the personalization of adaptive learning experiences. This study also formulates an idea engineering concept in the form of an integrated platform, combining AI, NLP, and gamification within a single learning ecosystem. The study concludes that Computer Science plays a role that is both strategic and ambiguous as a transformative solution as well as a source of linguistic challenges that must be addressed proactively within the Indonesian language education ecosystem.